Structure comparison and optical properties of Na7Mg4.5(P2O7)4: a sodium magnesium phosphate with isolated P2O7 units. (5th April 2017) - Ma, Ruru; Yang, Yun; Pan, Shilie; Sun, Yanzhou; Yang, Zhihua
Abstract : The crystal structure of Na7 Mg4.5 (P2 O7 )4 comprises a parallelogram channel composed of corner/edge-sharing isolated [P2 O7 ] dimers and a Na(2)O5 polyhedra to form a 3D framework and has an ultraviolet (UV) cut-off edge of about 210 nm. Abstract : Herein, a sodium magnesium diphosphate, Na7 Mg4.5 (P2 O7 )4, was synthesized via a standard solid-state reaction method, and a single crystal X-ray diffraction method was adopted to determine its crystal structure. It was found that it crystallizes in the triclinic system with the space group P 1̄. The crystal structure of Na7 Mg4.5 (P2 O7 )4 features a parallelogram channel composed of corner/edge-sharing isolated [P2 O7 ] dimers and a Na(2)O5 polyhedra to form a 3D framework. Thermal behaviors indicate that Na7 Mg4.5 (P2 O7 )4 congruently melts and IR spectrum shows the existence of the P2 O7 groups. Moreover, Na7 Mg4.5 (P2 O7 )4 possesses an experimental band gap of 5.90 eV and an ultraviolet (UV) cut-off edge of about 210 nm, which was confirmed via diffuse reflection spectrum. To analyze the contribution of the atomic orbitals to the energy band, band structures and partial density of states (PDOS) of Na7 Mg4.5 (P2 O7 )4 have also been reported.